Use of Alternative Materials in Sustainable Geotechnics: State of World Knowledge and Some Examples from Poland - Małgorzata Jastrzębska (Applied Sciences)
Geotechnical engineering projects carried out within the framework of the low-emission economy and the circular economy are the subject of many publications. Some of these studies present the use of various waste materials, as soil additives, for improving geomechanical behavior/properties. Many of these materials are eagerly used in geoengineering applications, primarily to strengthen weak subsoil or as a base layer in road construction. Information on individual applications and types of these materials is scattered. For this reason, this article briefly discusses most of the major waste materials used for achieving weak-soil improvement in geoengineering applications, and highlights pertinent bibliographic sources where relevant details can be found. The presented list includes waste from mines, thermal processes, end-of-life car tires, chemical processes (artificial/synthetic fibers), and from construction, renovation and demolition works of existing buildings and road infrastructure. The presentation of various applications is supplemented with three dynamically developing innovative technologies based on nanomaterials, microorganisms (MICP, EICP) and lignosulfonate. In addition to the positive impact of using waste (or technologies) instead of natural and raw materials, the paper encourages the reader to ponder whether the waste used really meets the criteria for ecological solutions and what is the economic feasibility of the proposed implementations.